2016
DOI: 10.3325/cmj.2016.57.141
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in sedentary men is linked to higher heart rate, sympathetic activity, and insulin resistance but not inflammation or oxidative stress

Abstract: AimTo compare anthropometric parameters, body composition, hormonal and inflammatory profiles, oxidative stress indices, and heart rate variability (HRV) in Heliobacter pylori (H.pylori) positive and negative healthy sedentary participants.MethodsAmong 30 recruited apparently healthy male participants (age between 20 and 40) enrolled in this cross-sectional study, 18 were H.pylori negative and 12 were positive (stool antigen test). Participants underwent routine physical examination and body composition determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…The opposite effects are mediated by anti-inflammatory interleukin-10 [104] and the spleen plays a particularly important role in these regulatory interactions [105]. The autonomic nervous system may also be involved in regulation of interactions of local inflammatory conditions and oxidative stress [106]. Autonomic output is actively involved in the regulation of glucose homeostasis and can adjust the rates of glucose production and utilization independently of hormonal influences [107].…”
Section: Inflammation Insulin Resistance and Redox Homeostasismentioning
confidence: 99%
“…The opposite effects are mediated by anti-inflammatory interleukin-10 [104] and the spleen plays a particularly important role in these regulatory interactions [105]. The autonomic nervous system may also be involved in regulation of interactions of local inflammatory conditions and oxidative stress [106]. Autonomic output is actively involved in the regulation of glucose homeostasis and can adjust the rates of glucose production and utilization independently of hormonal influences [107].…”
Section: Inflammation Insulin Resistance and Redox Homeostasismentioning
confidence: 99%
“…It was demonstrated that Amaranth oil supplementation provided significant improvement of gastric mucosa morphological pattern and also had a positive effect on heart rate variability [5]. In a separate study we demonstrated that H. pylori in apparently healthy sedentary young male subjects is associated with higher heart rate, sympathetic activity and insulin resistance, however, we detected no changes in parameters reflecting inflammatory profile, metabolic parameters or oxidative stress [6][7][8]. In summary, there is a growing evidence of systemic metabolic effects of H. pylori infection not only in patients with overt gastrointestinal disorders, but also in apparently asymptomatic healthy subjects.…”
mentioning
confidence: 56%
“…The opposite effects are mediated by anti-inflammatory interleukin-10 [104] and the spleen plays a particularly important role in these regulatory interactions [105]. The autonomic nervous system may also be involved in regulation of interactions of local inflammatory conditions and oxidative stress [106]. Autonomic output is actively involved in regulation of glucose homeostasis and can adjust the rates of glucose production and utilization independently of hormonal influences [107].…”
Section: Inflammation Insulin Resistance and Redox Homeostasismentioning
confidence: 99%